IMPLEMENTASI MANAJEMEN KURIKULUM MERDEKA DI SMA NEGERI 1 CIBUNGBULANG - Rahmawati, Ima; Nurasiyah, Siti; Ihsan, Muzhir; Setiawan, Waslim; Lestari, Fitri (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
One of the major impacts caused by the post-COVID-19 pandemic is the change in education curriculum policies. The education curriculum in Indonesia at home has become an independent curriculum in order to catch up with the loss and lagging behind of learning quality during covid 19. The implementation of the independent curriculum was tested in driving schools. SMA Negeri 1 Cibungbulang is one of the driving schools targeted for the implementation of the independent curriculum. This study is aimed at knowing how to implement the independent curriculum at SMA Negeri 1 Cibungbulang. This study used descriptive qualitative methods with data collection techniques in the form of interviews and observations. The results showed that SMA Negeri 1 Cibungbulang has implemented the independent curriculum since 2021, and has reached the advanced level by the end of the 2024 school year, meaning that the implementation of the curriculum is very good. Therefore, entering the 2024/2025 school year, SMA Negeri 1Cibungbulang towards Implementation of the Independent Curriculum without assistance both in terms of material and funding